(untitled) (Journal of Statistics on Health Decision, 2022)
The COVID-19 pandemic disease, caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (Sars-CoV-2), has affected millions of people worldwide. Clinical practice highlights that the number of patients with COVID-19 diagnosed with bacterial infections during periods of hospitalization is increasing. Rapid characterization of co-infection is essential in the treatment of most patients with COVID-19, as it can result in failure of antimicrobial therapy. Some studies report the prevalence of variable coinfection among patients with COVID-19, however, it can be up to 50% in patients who did not survive. (1, 2) The present study aims: - To assess the occurrence of associations between COVID-19 and bacterial infections in patients hospitalized at Centro Hospitalar Baixo Vouga – Aveiro between April 1, 2020 and December 31, 2021. - Contribute to the definition of pharmacological therapy strategies in patients with mixed, bacterial and Sars-CoV-2 infections.